ADENOMYOEPITHELIOMA WITH CARCINOMA; EPITHELIAL-MYOEPITHELIAL CARCINOMA WITH EARLY PULMONARY METASTASIS - khan, Muhammad Umair (Journal of Ayub Medical College Abbottabad, 2024)
Adenomyoepithelioma (AME) is a rare variant of breast neoplasm. It is a biphasic tumour characterized by small epithelial-lined spaces with inner luminal cells and outer of abluminal (myoepithelial) cells. Either - or both - of these two cells may rarely undergo malignant transformation. We present a case of a 61-year-old lady who arbored a mass in her right breast. She presented with few left sided pulmonary nodules as well and was initially diagnosed with extensive DCIS on core biopsy. Lung biopsy of nodule was diagnosed as epithelial myoepithelial neoplasm. Ultimately, modified radical mastectomy and pneumonectomy was performed. The final histopathological diagnosis turned out to be malignant. Adenomyoepithelioma with carcinoma; epithelial-myoepithelial carcinoma of breast with pulmonary metastasis. The malignant transformation of adenomyoepithelioma has been documented in only a limited number of cases. Benign AME often undergoes treatment through wide local excision, given its rare local recurrence. In contrast, the approach to malignant AME typically involves a mastectomy, with or without a lymph node biopsy. Metastases may manifest several years’ post-primary diagnosis, even in cases of AMEs lacking atypical histological features. However, in our case metastasis was seen with in first four months of clinical presentation. Adenomyoepithelioma with carcinoma is an exceptionally rare neoplasm that may present with early metastasis, challenging the conventional findings of late metastasis as reported in studies. Consequently, the behaviour and prognosis of this entity remains a grey area, necessitating further exploration with a substantial sample size.